2017
DOI: 10.3390/ijms18010103
|View full text |Cite
|
Sign up to set email alerts
|

Dark and Photoinduced Cytotoxic Activity of the New Chlorophyll-a Derivatives with Oligoethylene Glycol Substituents on the Periphery of Their Macrocycles

Abstract: In the present work, we investigated the dark and photoinduced cytotoxic activity of the new chlorophyll-a derivatives which contain the substituents of oligoethylene glycol on the periphery of their macrocycles. These compounds were tested using human cell lines to estimate their potential as photosensitizers for photodynamic therapy of cancer. It was shown that all the tested compounds have expressed photoinduced cytotoxic activity in vitro. Detailed study of the biological activity of one of the most perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(29 reference statements)
1
7
0
6
Order By: Relevance
“…The photosensitizing efficiencies of metal-free chlorins, virtually coincides with the data reported earlier. [21,30,31] IC 50 in the cells incubated in the dark exceeds IC 50 in illuminated samples by two or more orders of magnitude. The photodamaging effect of complexes (Cu-1-Cu-3) is somewhat weaker, however, the ability of these compounds to exert a photosensitizing cell killing is manifested quite clearly.…”
Section: Measurement Of the Quantum Yields Of Singlet Oxygen Generatimentioning
confidence: 94%
See 2 more Smart Citations
“…The photosensitizing efficiencies of metal-free chlorins, virtually coincides with the data reported earlier. [21,30,31] IC 50 in the cells incubated in the dark exceeds IC 50 in illuminated samples by two or more orders of magnitude. The photodamaging effect of complexes (Cu-1-Cu-3) is somewhat weaker, however, the ability of these compounds to exert a photosensitizing cell killing is manifested quite clearly.…”
Section: Measurement Of the Quantum Yields Of Singlet Oxygen Generatimentioning
confidence: 94%
“…The dark and photoinduced toxic activity of chlorins was investigated as described in refs. [21,30,31]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] В то же время, внедрение фрагмента олигоэтиленгликоля, а также его положение в хлориновом макроцикле может оказывать влияние на темновую цитотоксичность соединения. [13] В связи с этим в настоящей работе синтезированы новые порфиринаты переходных металлов (меди, цинка и никеля) с фрагментом диэтиленгликоля (ДЭГ) на периферии макроцикла (Cu-1, Cu-3, Ni-1, Ni-3, Zn-1, Zn-3, Схема 1) и исследована темновая цитотоксическая активность вновь и ранее синтезированных комплексов (Cu-2, Ni-2, Zn-2) в сравнении с соответствующими безметальными хлоринами (1-3) на линиях опухолевых клеток HeLa с целью выявления перспективных темновых противоопухолевых цитостатиков.…”
Section: Introductionunclassified
“…In recent years, the bis‐nuclear compounds have been attracted great interests in the drug development since they usually exhibited some unique properties such as enhanced biological activities compared with the corresponding mono‐nuclear analogs . Bis‐isatin derivatives demonstrated promising anti‐cancer, anti‐viral and anti‐TB activities,, and the structure‐activity relationship (SAR) revealed that the linker between the two isatin moieties played a pivotal role in exert their biological activities . Diethylene glycol fragment has the potential to exert diverse noncovalent interactions, which may facilitate the bind with active site, and some diethylene glycol tethered derivatives possess considerable biological activities ,.…”
Section: Introductionmentioning
confidence: 99%